2015
DOI: 10.1212/wnl.0000000000002067
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI substrates of cognitive impairment in neuromyelitis optica

Abstract: In patients with NMO, WM tract integrity disruption was identified in both CP and CI groups. GM atrophy, particularly in the DGM, was only found in the CI group. Hippocampal volume is the main MRI predictor of cognition in NMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
73
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 39 publications
14
73
6
Order By: Relevance
“…The data presented here appear broadly consistent with the majority of studies evaluating Asian populations, which reported significant thalamic atrophy in patients with NMOSD compared with HCs . However, two previous studies evaluating Caucasian patients reported no significant differences in the thalamic volumes between patients with NMOSD and HCs .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The data presented here appear broadly consistent with the majority of studies evaluating Asian populations, which reported significant thalamic atrophy in patients with NMOSD compared with HCs . However, two previous studies evaluating Caucasian patients reported no significant differences in the thalamic volumes between patients with NMOSD and HCs .…”
Section: Discussionsupporting
confidence: 90%
“…Of the three previous studies of DGM volume in patients with NMOSD that included an analysis of cognitive functioning , one excluded our comparison due to the use of limited cognitive assessment tools . Of the two remaining studies, both showed significant thalamic atrophy associated with CI , which is consistent with the data presented here. The latter of these studies also described associations between hippocampal, putamenal and accumbens atrophy and CI , although these results were not replicated in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…Neurons are also important components of NVU and are thought to be the driving force behind neurovascular coupling due to their high energy demand. Volume reduction and neuronal loss in GM have also been observed in NMO, which is partly due to the axonal degeneration secondary to optic neuritis and myelitis or may be a direct consequence of neuronal damage in GM (Duan et al, ; Kawachi & Lassmann, ; Liu et al, ; Pichiecchio et al, ; Saji et al, ; von Glehn et al, ; Wang, Zhang et al, ). The observed neuron damage may also account for the reduced neurovascular coupling in NMO.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte damage is thought to be a key pathological characteristic of NMO (Kawachi & Lassmann, ; Takeshita et al, ), which may disrupt the NVU and eventually result in abnormal neurovascular coupling. In addition, the previously reported neuronal (Duan et al, ; Liu et al, ; Pichiecchio et al, ; Saji et al, ; von Glehn et al, ; Wang, Zhang et al, ) and vascular impairments (Sanchez‐Catasus et al, ; Takeshita et al, ) could also affect neurovascular coupling in NMO. Based on the evidence of astrocyte damage, neuronal loss, and vascular impairments in NMO, we hypothesized that patients with NMO would show alterations in neurovascular coupling.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation